Comparison of factors associated with the evidence-practice gap as perceived by Japanese and Brazilian dentists - Kakudate, Naoki; Yokoyama, Yoko; Tagliaferro, Elaine Pereira da Silva [UNESP]; Sumida, Futoshi; Matsumoto, Yuki; Gordan, Valeria V; Gilbert, Gregg H (Elsevier, 2024)
Objectives: To identify 1) factors of the evidence-practice gap (EPG) in Japan and Brazil as perceived by dentists and compare these factors between two countries, and 2) mechanisms to close this EPG. Methods: The study employed a cross-sectional design by administering a web-based questionnaire to 136 Japanese and 110 Brazilian dentists. The survey queried dentists’ reports of which factors possibly cause an EPG, using a newly developed 20-item questionnaire. Results: An international comparison of 20 items related to factors of the EPG between Japan and Brazil revealed that Dentists' own experiences are sometimes given priority over evidence and Dentists' own thoughts are sometimes given priority over evidence were common factors to both countries, with over 80 % agreement. In logistic regression, Insufficient opportunity to learn about evidence in dental education at universities, Evidence-based treatments are sometimes not covered by the dental insurance system, and Insufficient evidence which helps dentists choose an appropriate treatment for a patient after careful consideration of his/her own background were significantly associated with the EPG in Japan (p < 0.05). In Brazil, Insufficient case reports in which evidence-based dentistry (EBD) is applied to clinical practice and Image-based information and devices used for diagnosis vary depending on individual dentists were significantly associated with the EPG (p < 0.05). Conclusions: This study suggests that EPG could be improved in Japan: by promoting EBD education at universities, improving the dental insurance system, and accumulating evidence according to patient background; and in Brazil: by promoting EBD case reports and standardizing diagnostic information and devices. Clinical Significance: Two factors of EPG common to Japan and Brazil, namely the prioritization of dentists' own experiences and thoughts over evidence, are urgent issues for improving EPG. In addition, it will be necessary to address the country-specific factors of EPG that were identified in this study.
Keywords: Evidence-based dentistry; Evidence-practice gap; International comparison; Minimal intervention dentistry; Practice-based research